2018
DOI: 10.1155/2018/9651254
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Pretreatment Neutrophil/Lymphocyte Ratio and Platelet/Lymphocyte Ratio in Patients with Diffuse Large B-Cell Lymphoma

Abstract: It is generally believed that there is correlation between cancer prognosis and pretreatment PLR and NLR. However, there are limited data about their role in diffuse large B cell lymphoma (DLBCL). This study aims to determine the prognostic value of pretreatment PLR and NLR for patients who have DLBCL. The associations between clinical characteristics and NLR and PLR were evaluated among 182 DLBCL patients from January 2005 to June 2016. The optimal cutoff values for high PLR (⩾150) and NLR (⩾2.32) in prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
0
31
0
1
Order By: Relevance
“…At present, a number of basic experiments and clinical researches worldwide have been conducted to find exact serological laboratory indicators in the hope of a more reliable and accurate judgment of patients with various malignant tumors. Neutrophil/lymphocyte ratio,28 lymphocyte/monocyte ratio,29 serum albumin30 and plasma fibrinogen31 have been confirmed to have an association with prognosis of special kinds of cancers.…”
Section: Discussionmentioning
confidence: 93%
“…At present, a number of basic experiments and clinical researches worldwide have been conducted to find exact serological laboratory indicators in the hope of a more reliable and accurate judgment of patients with various malignant tumors. Neutrophil/lymphocyte ratio,28 lymphocyte/monocyte ratio,29 serum albumin30 and plasma fibrinogen31 have been confirmed to have an association with prognosis of special kinds of cancers.…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, NLR as an in ammation indicator has been well studied in various in ammation associated pathological conditions [10][11][12][13]. Higher NLR was correlated with more advanced disease stage in autoimmune disease [17,18] and it was proved to be an independent prognosis factor in infections disease [11,19], diffuse large B-cell lymphoma [20,21], and so on. Whilst, a higher NLR predicts increased 30-day mortality in critically ill patients [13,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The antitumour activity of inflammation and the associated immune activation, induce tumour growth and progression. Inflammation is an independent predictor for response to therapy, event-free survival and overall survival (OS) in diffuse large B-cell lymphoma (DLBCL) patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Kang et al demonstrated that PLR had significant association with a poor prognosis in patients with non-Hodgkin's lymphoma, treated by R-CHOP [16]. Wang et al reported that high PLR was associated with shorter OS and PFS in patients with DLBCL [10], also Seo et al found that PLR showed independent significance in patients with advanced stage marginal zone lymphoma treated with rituximab, vincristine, cyclophosphamide, and prednisone protocol [17]. Retrospective analysis of 283 myeloma patients showed that inverse PLR had predictive value for OS and PFS [18].…”
Section: Discussionmentioning
confidence: 99%